Normal soaking extraction (NSE) of rotenone from Derris elliptica - Zubairi, Saiful Irwan; Sarmidi, M. R.; Aziz, R. A.; Ramli, M. K. A.; Latip, R.; Nordin, N. I. A. (2004)
Derris elliptica or the tuba plant contains rotenone, bio-active compound known that has the potential to be used as bio-pesticide. Bio-pesticide is the best-known alternative bio-pesticide which has the potential to replace the use of conventional pesticides, as it is more environmentally friendly. The main objective of the paper is to obtain the best extraction solvent for optimizing the yield in rotenone extraction. Rotenone was extracted from Derris root using three different parts of roots and three types of solvent in Normal Soaking Extraction (NSE). The types of Derris roots are: (1) Fine root (2) Coarse root (3) Stem. The three types of solvent system are: (1) Acetone 95 % (v/v), (2) Chloroform 99.9 % (v/v) and (3) a mixture of ethanol: H2O (9:1) added with oxalic acid (1mg/ml). The liquid crude extracts were further cleaned up to remove the fine debris of roots. The presence of rotenone was confirmed using qualitative analysis Thin Layer Chromatography (TLC) and thereupon the determination of rotenone content was carried out using High Performance Liquid Chromatography (HPLC). From the results obtained, it was found that the Normal Soaking Extraction (NSE) using acetone 95 % (v/v) was the best method to extract the highest yield of rotenone; 1.14 % (w/w).